Drug sensitivity of single cancer cells is predicted by changes in mass accumulation rate - Stevens, Mark M; Maire, Cecile L; Chou, Nigel; Murakami, Mark A; Knoff, David S; Kikuchi, Yuki; Kimmerling, Robert J; Liu, Huiyun; Haidar, Samer; Calistri, Nicholas L; Cermak, Nathan; Olcum, Selim; et al. (Nature biotechnology, 2016)
The efficacy of cancer drugs is profiled by measuring changes in the mass of single tumor cells. Assays that can determine the response of tumor cells to cancer therapeutics could greatly aid the selection of drug regimens for individual patients. However, the utility of current functional assays is limited, and predictive genetic biomarkers are available for only a small fraction of cancer therapies. We found that the single-cell mass accumulation rate (MAR), profiled over many hours with a suspended microchannel resonator, accurately defined the drug sensitivity or resistance of glioblastoma and B-cell acute lymphocytic leukemia cells. MAR revealed heterogeneity in drug sensitivity not only between different tumors, but also within individual tumors and tumor-derived cell lines. MAR measurement predicted drug response using samples as small as 25 μl of peripheral blood while maintaining cell viability and compatibility with downstream characterization. MAR measurement is a promising approach for directly assaying single-cell therapeutic responses and for identifying cellular subpopulations with phenotypic resistance in heterogeneous tumors.